Failed entrepreneurship in a heterotopia: the story of Villa Ahumada - Montiel, Oscar (2021)
Abstract Purpose The heterotopia is frequently portrayed as a third space in organization studies, characterized by its flexibility and receptivity to innovation. Rural entrepreneurship, embodied in the heterotopic space of community-based enterprises (CBEs), is a key concept in emerging economies. Understanding the CBE’s economic and social dynamics is vital for the genesis of entrepreneurship in these spaces, for regional development and for national economies. This paper aims to deep dive into the group dynamics of Villa Ahumada (VA), a well-known subspace located close to the Mexico–USA border, which, despite its market potential, has not been able to support the collectivization required of a CBE.